103k views
5 votes
Solve by elimination 10x-5y=-25 -2x+2y=0

1 Answer

2 votes

Answer:

(- 5, - 5 )

Explanation:

Given the 2 equations

10x - 5y = - 25 → (1)

- 2x + 2y = 0 → (2)

Multiplying (2) by 5 and adding to (1) will eliminate the term in x

- 10x + 10y = 0 → (3)

Add (1) and (3) term by term

5y = - 25 ( divide both sides by 5 )

y = - 5

Substitute y = - 5 into either of the 2 equations and solve for x

Substituting in (1)

10x - 5(- 5) = - 25, that is

10x + 25 = - 25 ( subtract 25 from both ides )

10x = - 50 ( divide both sides by 10 )

x = - 5

Solution is (- 5, - 5 )

User Feather
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.